Dependent interviewing and sub-optimal responding - Johannes Eggs; Annette Jäckle (University of Essex, Institute for Social and Economic Research (ISER), 2014)
With proactive dependent interviewing respondents are reminded of the answer they gave in the previous interview, before being asked about their current status. We examine the risk that respondents falsely confirm the answers from the previous interview as still applying, using data from a panel survey in which preload data about receipt of welfare benefit contained errors. A large proportion of respondents confirmed the false preload. Respondents with a more complex history of receipt, according to linked administrative records, were more likely to confirm. Personality also seemed to matter. Predictors of satisficing and characteristics of the survey and interviewer were not predictive of confirming the false preload.
Keywords: C81; C83; 330; measurement error; validation; record linkage; panel survey; welfare benefit; satisficing